1995
DOI: 10.1021/ed072p182
|View full text |Cite
|
Sign up to set email alerts
|

Acid Volatile Sulfides (AVS) in Sediment: An Environmental Chemistry Experiment

Abstract: Experimental procedure for measuring acid volatile sulfides in environmental samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…First and foremost, to our knowledge, it is the first laboratory experiment for undergraduate students to quantify microplastic (with an emphasis on microfibers) pollution in soil samples. Environmental concerns are of major importance to many students, and although there are many published environmental chemistry laboratory experiments, some of which deal with plastics, there are none that allow students to quantify microplastics pollution in their environment. Second, this laboratory experiment incorporates several key topics (pH, solution concentration calculations, etc.) learned in virtually any nonmajors’ or majors’ chemistry course within a single laboratory experiment.…”
Section: Introductionmentioning
confidence: 99%
“…First and foremost, to our knowledge, it is the first laboratory experiment for undergraduate students to quantify microplastic (with an emphasis on microfibers) pollution in soil samples. Environmental concerns are of major importance to many students, and although there are many published environmental chemistry laboratory experiments, some of which deal with plastics, there are none that allow students to quantify microplastics pollution in their environment. Second, this laboratory experiment incorporates several key topics (pH, solution concentration calculations, etc.) learned in virtually any nonmajors’ or majors’ chemistry course within a single laboratory experiment.…”
Section: Introductionmentioning
confidence: 99%
“…These sulfides likely dominate the CRS within the gabbros. As mentioned previously, the AVS is reduced sulfur contained within unstable products that almost always form as a result of microbial activity at low temperatures (<120°C; Brouwer, 1995; Rickard & Morse, 2005), this may be also the case for the THF and means that the AVS in the study area originated mainly from low‐temperature microbial activity, indicating that the AVS in the gabbro samples formed when the cooled gabbro was close to or exposed at the seafloor.…”
Section: Discussionmentioning
confidence: 65%
“…Sulfur occurs in three main forms: acid‐volatile sulfur (AVS), chromium‐reduced sulfur (CRS), and sulfate–sulfur (SS). AVS has been experimentally defined and represents the amount of reduced sulfur (H 2 S) released by acidification (Brouwer, 1995). Rickard and Morse (2005) suggested that AVS is reduced sulfur contained within unstable products that almost always form as a result of microbial activity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the interference of HS – has been studied here for the first time. Hydrogen sulfide is a common component of the coastal environment generated by bacterial metabolism. , Sulfide is found under anaerobic conditions such as the sediment covered with or inundated by seawater. When CO 2 levels in these environments need to be determined, H 2 S will cause interference to the traditional Severinghaus CO 2 probe because it is able to diffuse through the gas permeable membrane as a neutral species as well and change the pH of the inner NaHCO 3 in analogy to CO 2 .…”
Section: Resultsmentioning
confidence: 99%